ANALISIS RANCANG BANGUN KNOWLEDGE MANAGEMENT SYSTEM UNTUK MEMBENTUK SHARING CULTURE MATERI BAHAN AJAR BERBASIS WEB - Danny Manongga; Reni Veliyanti (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2018)
Abstract The implementation of knowledge sharing with a system by sharing several web-based teaching materials, may be a solution for STEKOM needs. Lack of lecturers’policy and culture to implement knowledge management (knowledge sharing)of the web-based teaching materialsresulting in lecturer's knowledge cannot be shared well. The purpose of this research is for implementing knowledge management system as teaching material for improving the competence of STEKOM lecturers. This research uses the development of 10-step knowledge management roadmap method system made by Amrit Tiwana, 1999 and summarized into 4 phases, i.e.: 1. evaluation of infrastructure; 2. analysis, design and development of KMS; 3. deployment system; 4. evaluation of system design methods. Results of this research indicated that operation of the KMS has a great opportunity in terms of knowledge transfer by forming a sharing culture of web-based teaching materials on STEKOM. This constitute as an alternative for improving the teaching quality . Sharing of teaching material not only carried out in the internal environment of the STEKOM branch, but also among lecturers of STEKOM branch and between STEKOM lecturers and students